2023
DOI: 10.3390/biology12050672
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR Signaling Pathway in HPV-Driven Head and Neck Carcinogenesis: Therapeutic Implications

Abstract: High-risk human papillomaviruses (HR-HPVs) are the causal agents of cervical, anogenital and a subset of head and neck carcinomas (HNCs). Indeed, oropharyngeal cancers are a type of HNC highly associated with HR-HPV infections and constitute a specific clinical entity. The oncogenic mechanism of HR-HPV involves E6/E7 oncoprotein overexpression for promoting cell immortalization and transformation, through the downregulation of p53 and pRB tumor suppressor proteins, among other cellular targets. Additionally, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 146 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…It has been well documented that E6 and E7 proteins of high-risk human papillomaviruses (HPVs) bind to and degrade p53 and pRb. E6 recruits the intracellular ubiquitin ligase E6AP, which is then ubiquitinated during the assembly of the E6/E6AP/p53 complex and subsequently induces proteasome-dependent p53 degradation ( Li et al., 2019 ), E7 not only inhibits pRb activity but also promotes its degradation ( Mir et al., 2023 ), leading to the loss of their tumor suppressor activities ( Aguayo et al., 2023 ) ( Figure 1 ). The downregulation of these tumor repressors enables uncontrolled cell growth and contributes to HPV-associated cancers, such as cervical cancer.…”
Section: Interaction Between Viral Proteins and Host Proteinsmentioning
confidence: 99%
“…It has been well documented that E6 and E7 proteins of high-risk human papillomaviruses (HPVs) bind to and degrade p53 and pRb. E6 recruits the intracellular ubiquitin ligase E6AP, which is then ubiquitinated during the assembly of the E6/E6AP/p53 complex and subsequently induces proteasome-dependent p53 degradation ( Li et al., 2019 ), E7 not only inhibits pRb activity but also promotes its degradation ( Mir et al., 2023 ), leading to the loss of their tumor suppressor activities ( Aguayo et al., 2023 ) ( Figure 1 ). The downregulation of these tumor repressors enables uncontrolled cell growth and contributes to HPV-associated cancers, such as cervical cancer.…”
Section: Interaction Between Viral Proteins and Host Proteinsmentioning
confidence: 99%
“…In HNSCC, understanding the molecular pathways and predicting patient outcomes is greatly aided by the use of various IHC markers, especially in the context of HPV infection. [11,12]. The role of PIK3CA in HPV-positive oropharyngeal squamous cell carcinoma was studied by Chiosea et al (2013) [13].…”
Section: Immunohistochemical (Ihc) Markers (P53 Pik3ca)mentioning
confidence: 99%
“…Salazar et al (2014) and Smith et al (2010) have identified p53 as important markers associated with survival in HNSCC [ 9 , 10 ]. Aguayo et al (2023) and Kommineni et al (2015) studied the significance of PIK3CA mutations in the PI3K/AKT/mTOR signalling pathway [ 11 , 12 ]. The role of PIK3CA in HPV-positive oropharyngeal squamous cell carcinoma was studied by Chiosea et al (2013) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that HPV oncoproteins induce cell cycle progression by inhibiting several tumor suppressors, including p53, PDZ, and retinoblastoma, resulting in tumor initiation and development [ 81 , 82 ]. PI3K/AKT/mTOR pathway, as one of the central signaling routes regulated in HPV‐related cancers, was implicated in regulating cell proliferation, migration, invasion, and angiogenesis [ 83 ]. The over-activation of PI3K/AKT signaling was reported in cervical squamous cell carcinomas like cervical cancer [ 84 ].…”
Section: Introductionmentioning
confidence: 99%